Safety of direct oral anticoagulants in patients with liver disease: a systematic review and meta-analysis. Issue 3 (4th May 2023) - Zhao, Yan; Zhu, Liyao; Yang, Yang; Gao, Han; Zhang, Rui
ABSTRACT: Background: Direct oral anticoagulants (DOACs), such as apixaban, edoxaban, rivaroxaban, or dabigatran, are an effective treatment for atrial fibrillation (AF) and deep venous thromboembolism. We hope to evaluate the safety of DOACs versus warfarin/low molecular weight heparin (LMWH) in improving bleeding events in patients with different severity of the liver disease. Methods: We systematically searched the Cochrane Library, PubMed, and Embase databases for studies reporting the effects of DOACs in patients with liver cirrhosis. A random-effects model or fixed-effects model was selected to pool risk ratios (RR) and 95% confidence intervals (CI). Results: A total of 18 studies involving 41, 447 participants was included in this meta-analysis. Compare with warfarin/ LMWH, the use of DOACs significantly reduced the incidence of all bleeding (RR: 0.76; 95%CI: 0.66 to 0.87), major bleeding (RR: 0.51; 95%CI: 0.28 to 0.91), intracranial hemorrhage (RR: 0.50; 95%CI: 0.31 to 0.81), and gastrointestinal bleeding (RR: 0.76, 95% CI: 0.60 to 0.97), and all-cause death in patients with liver disease (RR: 0.77; 95%CI: 0.62 to 0.95). Similar results were observed in atrial fibrillation patients with liver disease and cirrhosis subgroups. Furthermore, the pooled estimates of the Child-Turcotte-Pugh (CTP) class indicated that DOACs reduced the incidence of all bleeding (RR: 0.61; 95%CI: 0.45 to 0.82), gastrointestinal bleeding (RR 0.55; 95%CI: 0.37 to 0.83), and all-cause death (RR: 0.62; 95%CI: 0.49 to 0.79) in patients with mild to moderate cirrhosis. Conclusions: Our study demonstrates that DOACs significantly reduce the risk of bleeding in patients with liver disease compared with warfarin/LMWH.